The Nationalism Attitude in the Philosophy of Batik Gebleg Renteng Value of Kulon Progo Regency - Andi Andoko; Warto Warto; Djono Djono (BIRCU, 2021)
This study aims to describe the philosophical values in Gebleg Renteng batik originating from Kulon Progo district, Special Region of Yogyakarta. The method used in this research is descriptive qualitative method. Sources of data were taken from books, journals and interviews as well as supporting documents related to research. The main characteristics in the research come from natural/reality backgrounds in the community by observing, interviewing, and reviewing documents. After the data is collected, the researcher analyzes and concludes the results of the data that has been obtained. The result of the research is that Gebleg Renteng batik is a typical batik from Kulon Progo district. The motifs are gebleg like the number eight combined into one bond (jointly), kacer birds, mangos teen fruit, blooming flower bud, binagun symbol, Kulon Progo logo and up and down pattern. From these various motives, values can be drawn, namely the attitude of nationalism. Values are always associated with ethics, morals so that the philosophical values in Gebleg Renteng batik can be used to instill an attitude of nationalism to the younger generation of the nation's successors so that Indonesia is maintained, sovereign and not colonized by foreign nations.